Dynamic thiol/disulfide homeostasis in patients with autoimmune subclinical hypothyroidism. (1st October 2016) - Ates, Ihsan; Altay, Mustafa; Yilmaz, Fatma Meric; Topcuoglu, Canan; Neselioglu, Salim; Erel, Ozcan; Yilmaz, Nisbet
ABSTRACT: Objective : The aim of this study was to investigate dynamic thiol/disulfide homeostasis in autoimmune subclinical hypothyroidism.Methods : Forty-eight patients with a new diagnosis of subclinical hypothyroidism due to Hashimoto thyroiditis who were not yet under medical therapy, and 48 healthy control subjects were enrolled. Thiol/disulfide homeostasis [native thiol–disulfide exchanges] was measured in both groups using the automated method developed by Erel and Neselioglu. An absolute difference of 0.5 between the total thiol and native thiol concentrations revealed the disulfide bond amount.Results : The native thiol level ( p = 0.014) and native thiol/total thiol ratio ( p = 0.001) were lower in patients with subclinical hypothyroidism than in the control group. Meanwhile, the disulfide level ( p = 0.004), disulfide/native thiol ratio ( p = 0.001), and disulfide/total thiol ( p = 0.001) ratio were higher in patients with subclinical hypothyroidism than in the control group. The antithyroid peroxidase and anti-thyroglobulin levels were positively correlated with the disulfide/native thiol ratio (r = 0.339, p = 0.019; r = 0.243, p = 0.023, respectively) and the disulfide/total thiol ratio (r = 0.133, p = 0.019; r = 0.238, p = 0.026, respectively) and negatively correlated with the native thiol/total thiol ratio (r = −0.292, p = 0.004; r = −0.233, p = 0.022, respectively).Conclusion : We found that thiol/disulfide homeostasis shifted to disulfide formation in patients with subclinical hypothyroidism and that thyroid autoantibodies were positively correlated with thiol oxidation. It is not clear whether abnormal thiol/disulfide homeostasis is a cause or a consequence in Hashimoto thyroiditis. Further studies are required.